2017
DOI: 10.17957/ijab/15.0334
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a High-efficiency Genetic Transformation System of Cucumber (Cucumis sativus) using Csexpansin 10 (CsEXP10) Gene

Abstract: Cucumber is one of the most important vegetable crops in the world. To establish an efficient genetic transformation system in cucumber, the role of different factors such as pre-cultivation time, acetosyringone concentration, infection time and cocultivation time that can influence the transformation, was evaluated. In addition, Csexpansin 10 (CsEXP10) gene was transformed into the cucumber genome to produce transgenic lines. The results showed that various optimal parameters such as 100 mg L -1 of kanamycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Wang et al [39] found that explants pre-cultured for 1 day grew more resistant shoots than explants used for direct infection, and the rate of resistant shoots increased from 11.1% to 27.3%; however, as the preculture time was prolonged, the cell division ability was weakened, and the transformation rate also began to decline. Similar conclusions were obtained by Sun et al [41]: with the progress of pre-culture, the bud induction rate first increased and then decreased, and number of shoots per explant (90.01% and 1.5, respectively). Fan et al [54] reported that compared with 1-2 d of pre-cultivation, a higher number of regenerated buds and resistant buds could be obtained in 3-7 d, considering that an excessive pre-culture time will lead to difficulties in later positive screening.…”
Section: Pre-culture Periodsupporting
confidence: 89%
See 1 more Smart Citation
“…Wang et al [39] found that explants pre-cultured for 1 day grew more resistant shoots than explants used for direct infection, and the rate of resistant shoots increased from 11.1% to 27.3%; however, as the preculture time was prolonged, the cell division ability was weakened, and the transformation rate also began to decline. Similar conclusions were obtained by Sun et al [41]: with the progress of pre-culture, the bud induction rate first increased and then decreased, and number of shoots per explant (90.01% and 1.5, respectively). Fan et al [54] reported that compared with 1-2 d of pre-cultivation, a higher number of regenerated buds and resistant buds could be obtained in 3-7 d, considering that an excessive pre-culture time will lead to difficulties in later positive screening.…”
Section: Pre-culture Periodsupporting
confidence: 89%
“…However, it was also observed that some materials did not take root well with MS medium alone [29]; therefore, auxin and its analogs were often added to the medium in some studies. These could promote the rooting of shoots and accelerate the rooting process of adventitious shoots [27,41]. In addition, thidiazuron is an exogenous hormone commonly used in the culture of unfertilized cucumber cells and ovules and plays a key role in inducing the stage of explant callus formation to somatic embryogenesis [42].…”
Section: Exogenous Hormonementioning
confidence: 99%
“…The Agrobacterium tumefaciens-mediated genetic transformation system is currently the most desirable transformation method for dicotyledonous plants. Its transformation efficiency is often influenced by strain type ( Jaiwal et al., 2001 ; Yadav et al., 2014 ; Chen et al., 2018 ), explant pre-culture time ( Miguel and Oliveria, 1999 ; Yao et al., 2013 ; Verma et al., 2014 ; Mishra et al., 2016 ), infection time ( Sgamma et al., 2015 ; Li et al, 2018b ; Huang et al., 2017 ), infection concentration ( Coolado et al., 2015 ; Sun et al., 2017 ) co-culture time ( Tao and Ling, 2006 ; Wu et al., 2017 ), and AS concentration and addition method ( Singh et al., 2017 ). Different plants or different parts of the same plant may require unique transformation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, these parameters were different in various literatures and also lack of enough details in the existing studies. All of these reasons leaded to browning, Agrobacterium pollution, vitrification shoots, low efficiency of genetic transformation [24], gene expression and genetic instability, which still perplex researchers. In order to improve the efficiency of genetic transformation, the effects of different concentrations of kanamycin on the regeneration of cotyledonary nodes by applying it in different transformation periods were analyzed in the present study.…”
Section: Introductionmentioning
confidence: 99%